Combination therapy for visceral leishmaniasis - Banjara, MR (International Journal of Infection and Microbiology, 2013)
DOI: http://dx.doi.org/10.3126/ijim.v2i2.8318 Int J Infect Microbiol 2013;2(2):32-33